The Academic Job Search: Steps for Success. Issue 1 (2nd January 2019) - Gray, Joey; Larson, Lincoln R.; Fernandez, Mariela; Duffy, Lauren N.; Sturts, Jill; Powell, Gwynn M.; Roberts, Kelsie
Abstract: The complex and uncertain academic job search is often a terrifying prospect for aspiring recreation and leisure scholars. New doctoral candidates are eager for meaningful lived experiences and useful advice regarding the steps for a successful job search, including finding the right opportunities, submitting applications, interviewing well, and negotiating effectively. In this article, we address the significant challenges and considerations doctoral students face throughout the academic job search process. By outlining some of the best practices and strategies for success through the lens of recreation and leisure studies, we hope to help readers know what to expect and how to prepare—ultimately converting the seemingly daunting task of finding the right academic job into an exciting and rewarding opportunity.